Maritime Cybersecurity: Tantangan Dan Strategi Keamanan Maritim Indonesia - Saskia Aulia Putri; Agussalim Burhanuddin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The existence of digital transformation in the development of the world, makes the maritime industry increasingly rely on technology to carry out navigation, communication, and logistics intermediaries. As the maritime industry continues to adopt digitalization and adapt, the need for strategy as well as strengthening cybersecurity becomes critical for the country. The increase in cybercrime and its vulnerabilities should make Indonesia more aggressively address or anticipate this problem. Although it is proven that indonesia in its initiation of a cybersecurity strategy has increased, Indonesia is seen as still lacking to show the nation's commitment in terms of cyber security, when compared to data from NCIS (National Cyber security Index) from 2016-2023 Indonesia is still far below its neighbor, Malaysia, which is also a maritime country. Through a qualitative approach, this article aims to explain the urgency of cybersecurity in the maritime sector, highlighting challenges and solutions to protect ships, ports, and maritime infrastructure from cyber threats in Indonesia.